Fever-Associated Supraventricular Tachycardia after 4CMenB Vaccination in an Infant - Erdem Gönüllü; Burcu Topçu; Naci Öner; Ahmet Soysal; Metin Karaböcüoğlu (Hindawi Limited, 2019)
Meningococcal serogroup B vaccine 4CMenB (Bexsero) is a new four-component protein vaccine developed to prevent Neisseria meningitidis serogroup B infections. Case. We report a girl with fever and supraventricular tachycardia (SVT) 6-8 hours after the second dose of 4CMenB. SVT was unresponsive to the first dose of adenosine but terminated after the fourth dose of adenosine. During three months of follow-up, she was free of further SVT attacks. Conclusion. This is the first report of ECG-proven SVT after 4CMenB vaccination. Even if fever is coexistent, SVT should be considered after persistent tachycardia and 4CMenB vaccination.